Preparation method of efficient and stable perovskite solar cell combining ionic compound interface modification and polymer material external packaging

By using 345FAn ionic compounds in perovskite solar cells for interface modification and using a combination of POE and PIB for low-temperature hot-press packaging, the problem of insufficient stability of perovskite solar cells is solved, and an efficient and stable perovskite solar cell is achieved.

CN119546047APending Publication Date: 2025-02-28NORTHWESTERN POLYTECHNICAL UNIV +1

Patent Information

Application Number
CN202411673796.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

Existing perovskite solar cells are prone to attenuation under conditions such as humidity, temperature, light and bias, resulting in insufficient device stability and difficult to meet practical application needs.

Method used

Low-temperature hot-press packaging was performed by combining ionic compound interface modification and external packaging of polymer materials by using 345FAn ionic compounds on perovskite films and using a combination of POE and PIB packaging materials.

Benefits of technology

The stability and photoelectric conversion efficiency of perovskite solar cells are significantly improved. The packaged devices can still maintain high efficiency in high temperature and high humidity environments, and the efficiency loss is less than 3%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119546047A_ABST
    Figure CN119546047A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an efficient and stable perovskite solar cell combining ionic compound interface modification and polymer material external packaging, and particularly relates to the field of solar cells. Comprising a substrate, a hole transport layer, a self-assembly molecular layer, a light absorption layer, an electron transport layer and a metal electrode layer which are sequentially laminated from bottom to top, wherein the material of the light absorption layer is a perovskite thin film modified by an ionic compound ammonium ligand, and the material of the perovskite thin film is a CsFAMA ternary perovskite precursor. And the photoelectric conversion efficiency and the operation stability of the perovskite cell are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of batteries, and in particular to a method for preparing a highly efficient and stable perovskite solar cell that combines interface modification of ionic compounds with external encapsulation of polymer materials. Background Art

[0002] In recent years, the photoelectric conversion efficiency of perovskite solar cells has continued to rise, and the highest certified efficiency of the device has reached 26.7%. However, since perovskite solar cells are prone to attenuation under conditions such as humidity, temperature, light and bias, the serious lack of device stability is a bottleneck for its application. Current research on the stability of perovskite devices focuses on the optimization of perovskite materials themselves and device packaging. In terms of the optimization of perovskite materials themselves, it mainly includes additive engineering, component engineering and interface engineering (Adv. Mater., 2022, 2108357). Currently reported modification materials include salts, small molecules and polymers, all of which have improved the performance of perovskite cells to varying degrees. However, due to the harsh working environment, the stability of current perovskite cells is still difficult to meet the actual development needs, so it is necessary to use polymer materials to externally encapsulate the device to further improve the stability of the device.

[0003] In terms of device packaging materials, current research mainly focuses on UV-curing packaging materials and vacuum hot pressing packaging materials. Dong et al. compared the packaging effects of three different types of epoxy resin materials (thermal curing, two-component and UV-curing epoxy resins) and found that perovskite cells encapsulated with UV-curing epoxy resins have better stability (ChemSusChem, 2016, 9, 2597-2603). However, the above materials all require UV curing or vacuum hot pressing during the packaging process, which increases the cost of device packaging. The vacuum high-pressure environment damages the perovskite, resulting in poor operating stability of the perovskite cell. Summary of the invention

[0004] The main purpose of the present application is to provide a method for preparing an efficient and stable perovskite solar cell that combines interface modification of ionic compounds and external encapsulation of polymer materials, aiming to solve the problem of poor operating stability of existing perovskite cells.

[0005] To achieve the above-mentioned objectives, the present application provides a high-efficiency and stable perovskite solar cell combining interface modification of ionic compounds and external packaging of polymer materials, comprising a substrate, a hole transport layer, a self-assembled molecular layer, a light absorbing layer, an electron transport layer and a metal electrode layer stacked in sequence from bottom to top; wherein the material of the light absorbing layer is a perovskite film modified with an ionic compound ammonium ligand, and the material of the perovskite film is a CsFAMA ternary perovskite precursor.

[0006] Optionally, the ionic compound ammonium ligand is 3,4,5-trifluoroaniline hydroiodide.

[0007] Optionally, it also includes: an encapsulation layer, which covers the surface of the metal electrode layer and is made of POE sealant; a first cover plate, which is located below the substrate; and a second cover plate, which covers the encapsulation layer; wherein the first cover plate and the second cover plate are both made of glass.

[0008] Optionally, the substrate is indium tin oxide glass; the material of the hole transport layer is nickel oxide, and the thickness of the hole transport layer is 18-22nm; the material of the self-assembled molecular layer is [4-(3,6-dimethoxy-9H-carbazole-9-yl)butyl]phosphonic acid or (2-(9H-carbazole-9-yl)ethyl)phosphonic acid, and the thickness of the self-assembled molecular layer is 4-6nm; the material of the electron transport layer is a mixture of [6,6]-phenyl C61 butyric acid methyl ester and fullerene, wherein the mass ratio of [6,6]-phenyl C61 butyric acid methyl ester and fullerene is 4:1, and the thickness of the electron transport layer is 50-60nm; the thickness of the light absorption layer is 745-755nm.

[0009] Optionally, the electrode layer includes a silver layer, or a stacked chromium layer and a gold layer, wherein the chromium layer is in contact with the electron transport layer.

[0010] To achieve the above-mentioned purpose, the present application also provides a method for preparing the above-mentioned efficient and stable perovskite solar cell combining ionic compound interface modification and polymer material external encapsulation, comprising: spin coating a nickel oxide solution on a substrate to form a hole transport layer; spin coating a self-assembly solution on the hole transport layer to form a self-assembled molecular layer; spin coating a perovskite precursor solution on the self-assembled molecular layer to form a perovskite film, and dripping an ionic compound ammonium ligand solution on the perovskite film to form a light absorption layer; spin coating a mixed solution of [6,6]-phenyl C61 butyric acid methyl ester and fullerene on the light absorption layer to form an electron transport layer; depositing a metal electrode layer on the electron transport layer, A perovskite battery device is obtained; the perovskite battery device is placed on a first cover plate, the first cover plate is in contact with a substrate; an encapsulation layer is placed on the metal electrode layer, and an electrode is arranged between the metal electrode layer and the encapsulation layer; wherein the material of the encapsulation layer is a POE sealant; a sealing ring is arranged on the first cover plate, so that the perovskite battery device and the encapsulation layer are located on the inner side of the sealing ring; a second cover plate is placed above the encapsulation layer to obtain a perovskite battery element; the perovskite battery element is laminated, wherein the lamination temperature of the first cover plate is 80-85°C, the lamination temperature of the second cover plate is 100-105°C, and the lamination time is 30-35s, to obtain a perovskite battery.

[0011] Optionally, the formation process of the light-absorbing layer is as follows: a CsFAMA ternary perovskite precursor solution is dropped onto the self-assembled molecular layer, spin-coated at a rotation speed of 1000-1100 rpm for 10-12 s, spin-coated at a rotation speed of 5000-5100 rpm for 40-42 s, and annealed at a temperature of 105-110°C for 20-22 min to form a perovskite film; wherein, during the spin coating process, an anti-solvent is dropped onto the spin-coated surface; at a rotation speed of 3500-4000 rpm, an ionic compound ammonium ligand solution is dropped onto the perovskite film, and annealed at a temperature of 100-110°C for 5-7 min to form a light-absorbing layer.

[0012] Optionally, the spin coating process of the hole transport layer is as follows: drop the nickel oxide solution on the substrate, spin coat at a rotation speed of 2000-2500 rpm for 30-35 seconds; and heat at a temperature of 150-155° C. for 10-20 minutes.

[0013] Optionally, the spin coating process of the self-assembled molecular layer is as follows: drop the self-assembly solution on the hole transport layer, and spin coat at a rotation speed of 3000-4000 rpm for 30-35 seconds; and anneal at a temperature of 100-110° C. for 10-15 minutes.

[0014] Optionally, the spin coating process of the electron transport layer is as follows: a mixed solution of [6,6]-phenyl C61 butyric acid methyl ester and fullerene is dropped onto the light absorbing layer, spin coated at a rotation speed of 3000-3500 rpm for 30-35 s, and annealed at a temperature of 60-65° C. for 5-7 min.

[0015] Compared with the prior art, the present invention has the following beneficial effects: The preparation method of the high-efficiency and stable perovskite solar cell combined with ionic compound interface modification and polymer material external encapsulation of the present invention, compared with the existing interface modification method, adopts 345FAn ionic compound with rich functional groups, NH 3+ Interaction occurs between PbI2 and NH 3+The terminal is electrically positive, which can provide strong adsorption for the IA and IPb anti-site defects in the perovskite, thus playing the role of passivating the defects. At the same time, the molecule contains abundant CF bonds, which can form intermolecular hydrogen bonds, achieve strong intermolecular connections and build a solid moisture-proof layer, greatly improving the hydrophobicity of the perovskite film, enhancing the intrinsic stability of the perovskite film, and thus improving the stability of the perovskite solar cell device; using a combination of POE and PIB packaging materials, combined with a low-temperature hot-pressing packaging process, this packaging method has almost no effect on the open-circuit voltage of the perovskite battery, and the device efficiency decay is less than 3%; at the same time, during the packaging process, the packaging temperature is lower than 110°C, and the packaging process does not require ultraviolet radiation or a vacuum environment, effectively avoiding the potential damage to the perovskite film during the packaging process.

[0016] The high-efficiency and stable perovskite solar cell combined with ionic compound interface modification and polymer material external encapsulation of the present invention is modified by 345FAn ionic compounds, and its photoelectric conversion efficiency can reach 25.38%. After aging in air for 1000 hours, it maintains 82.6% of the initial efficiency, which is improved in efficiency and operation stability compared with conventional perovskite cells; the photoelectric conversion efficiency of the encapsulated perovskite device is 24.15%, the efficiency loss of the encapsulated solar cell is ≤3%, and it operates for 2000 hours under 50-60°C maximum power point tracking to maintain 94.1% of the initial efficiency, which is reduced in efficiency loss compared with conventional cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a schematic diagram of the structure of a highly efficient and stable perovskite solar cell that combines ionic compound interface modification and polymer material external encapsulation in this application; Figure 2 A normalized PCE evolution diagram of a highly efficient and stable perovskite solar cell combining ionic compound interface modification and polymer material external encapsulation in this application; Figure 3 The short-circuit current density-open-circuit voltage curve of a highly efficient and stable perovskite solar cell combining ionic compound interface modification and polymer material external encapsulation in this application; Figure 4 This is a normalized SPO evolution diagram of a highly efficient and stable perovskite solar cell that combines ionic compound interface modification and polymer material external encapsulation in this application.

[0018] The realization of the purpose, functional features and advantages of this application will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0019] In order to make the purpose, technical solutions and advantages of this application clearer, the technical solutions in this application will be clearly and completely described below in conjunction with the drawings in this application. Obviously, the described embodiments are part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0020] The first embodiment of the present invention provides a highly efficient and stable perovskite solar cell combining ionic compound interface modification and polymer material external encapsulation, such as Figure 1 As shown, it includes a substrate, a hole transport layer, a self-assembled molecular layer, a light absorption layer, an electron transport layer and a metal electrode layer stacked in sequence from bottom to top; it also includes an encapsulation layer, a first cover plate and a second cover plate, the encapsulation layer covers the surface of the metal electrode layer, the material of the encapsulation layer is POE sealant, the second cover plate covers the top of the encapsulation layer, and the first cover plate is located below the substrate.

[0021] The material of the light-absorbing layer is a perovskite film modified by an ionic compound ammonium ligand, and the thickness of the light-absorbing layer is 745-755 nm; the perovskite precursor is a CsFAMA ternary perovskite precursor solution, and its chemical formula is (FA 0.98 MA 0.02 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05 )3; the ammonium ligand of the ionic compound is 3,4,5-trifluoroaniline hydroiodide (345FAn).

[0022] The substrate is indium tin oxide glass; the material of the hole transport layer is nickel oxide, and the thickness of the hole transport layer is 18-22nm; the material of the self-assembled molecular layer is [4-(3,6-dimethoxy-9H-carbazole-9-yl)butyl]phosphonic acid or (2-(9H-carbazole-9-yl)ethyl)phosphonic acid, and the thickness of the self-assembled molecular layer is 4-6nm; the material of the electron transport layer is a mixture of [6,6]-phenyl C61 butyric acid methyl ester and fullerene, the mass ratio of the two is 4:1, and the thickness of the electron transport layer is 50-60nm; the electrode layer includes a silver layer, or a chromium layer and a gold layer stacked in sequence; the thickness of the silver layer is 148-152nm, the thickness of the chromium layer is 5-10nm, and the thickness of the gold layer is 100-120nm.

[0023] In this embodiment, 345FAn has abundant functional groups, wherein the NH3+ in the 345FAn molecule interacts with PbI2, and NH3 +The terminal is electrically positive, which can provide strong adsorption for the IA and IPb anti-site defects in the perovskite, thus playing the role of passivating the defects. At the same time, the molecule contains abundant CF bonds, which can form intermolecular hydrogen bonds, achieve strong intermolecular connections and build a strong moisture-proof layer, greatly improving the hydrophobic properties of the perovskite film and enhancing the intrinsic stability of the perovskite film.

[0024] The second embodiment of the present invention provides a method for preparing the above-mentioned efficient and stable perovskite solar cell combining ionic compound interface modification and polymer material external encapsulation, which specifically comprises the following steps: Step S1, placing the indium tin oxide (ITO) glass in an ultrasonic cleaning tank, and cleaning it with a detergent-deionized water solution, acetone and ethanol in sequence for 15-20 minutes; drying it with nitrogen, and then treating it with ultraviolet ozone for 15-20 minutes; Step S2, spin coating a nickel oxide solution on the substrate to form a hole transport layer with a thickness of 18-22 nm; Specifically, the concentration can be 20 mg / mL −1 A nickel oxide (NiOx) solution is dropped onto the substrate and spin coated at a speed of 2000-2500 rpm for 30-35 seconds; and heated at a temperature of 150-155°C for 10-20 minutes.

[0025] Step S3, spin coating the self-assembly solution on the hole transport layer to form a self-assembled molecular layer with a thickness of 4-6 nm; Specifically, the product obtained in step S2 is transferred to a glove box, the self-assembly solution is dripped onto the hole transport layer, and the layer is spin-coated at a speed of 3000-4000 rpm for 30-35 seconds; and annealed at a temperature of 100-110° C. for 10-15 minutes.

[0026] In this embodiment, the self-assembly solution in this embodiment is an ethanol solution of [4-(3,6-dimethoxy-9H-carbazole-9-yl)butyl]phosphonic acid, and the concentration of [4-(3,6-dimethoxy-9H-carbazole-9-yl)butyl]phosphonic acid is 1.5 mg / mL -1 The self-assembly solution can also be an ethanol solution of (2-(9H-carbazole-9-yl)ethyl)phosphonic acid, the concentration of (2-(9H-carbazole-9-yl)ethyl)phosphonic acid is 2.2-2.5 mg / mL -1 Through the self-assembled molecular layer, the photogenerated holes are extracted and transmitted from the perovskite layer; at the same time, the electron migration is blocked, the charge recombination is avoided, the interface contact is optimized, and the interface energy barrier is reduced.

[0027] Step S4, spin coating a perovskite precursor solution on the self-assembled molecular layer to form a perovskite film, and dripping an ionic compound ammonium ligand solution on the perovskite film to form a light absorbing layer with a thickness of 745-755 nm; Specifically, in step S41, a CsFAMA ternary perovskite precursor solution is dripped onto the self-assembled molecular layer, and the solution is spin-coated at a rotation speed of 1000-1100 rpm for 10-12 s, and at a rotation speed of 5000-5100 rpm for 40-42 s. After the spin coating is completed, the product is transferred to a heating platform, and annealed at a temperature of 105-110° C. for 20-22 min to form a perovskite film, i.e., a MeO-4PACz film; wherein, during the spin coating process, an anti-solvent is dripped onto the spin coating surface, and the anti-solvent can be ethyl acetate, and the anti-solvent can accelerate the crystallization process of the perovskite film, improve the film quality, reduce defects, and thus improve the device performance; Step S42, within 2-3 seconds after the perovskite film is obtained, an ionic compound ammonium ligand solution is dripped onto the perovskite film at a rotation speed of 3500-4000 rpm, and annealed at a temperature of 100-110° C. for 5-7 minutes to form a light absorbing layer.

[0028] Furthermore, the preparation method of the CsFAMA ternary perovskite precursor solution is as follows: 1.62M lead iodide (PbI2), 0.09M cesium iodide (CsI), 0.11M lead bromide (PbBr2), 0.03M methylammonium bromide (MABr) and 1.61M formamidine iodide (FAI) are mixed in anhydrous N,N-dimethylformamide / dimethyl sulfoxide (DMF / DMSO) solvent, wherein the volume ratio of DMF to DMSO is 5:1, and the concentration of the mixed solution is 1.73M. After mixing, the mixture is stirred overnight to obtain a CsFAMA ternary perovskite precursor solution with the chemical formula (FA 0.98 MA 0.02 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05 )3. The ionic compound ammonium ligand solution is a chloroform (CF) solution of 3,4,5-trifluoroaniline hydroiodide, wherein the concentration of 3,4,5-trifluoroaniline hydroiodide is 0.5-1.5 mg / mL -1 .

[0029] Step S5, spin coating a mixed solution of [6,6]-phenyl C61 butyric acid methyl ester and fullerene on the light absorbing layer to form an electron transport layer with a thickness of 50-60 nm; Specifically, a mixed solution of [6,6]-phenyl C61 butyric acid methyl ester (PCBM, purity 99%) and fullerene (C60, purity 99.5%) is dripped onto the light absorbing layer, and spin-coated at a speed of 3000-3500 rpm for 30-35 seconds; and annealed at a temperature of 60-65°C for 5-7 minutes. The mass ratio of [6,6]-phenyl C61 butyric acid methyl ester to fullerene is 4:1.

[0030] Step S6, depositing a metal electrode layer on the electron transport layer by a thermal evaporation method to obtain a perovskite battery device; Step S7, placing the perovskite battery device on the first cover plate, the first cover plate is in contact with the substrate; placing an encapsulation layer on the metal electrode layer, and arranging an electrode between the metal electrode layer and the encapsulation layer; wherein the material of the encapsulation layer is POE sealant; arranging a sealing ring on the first cover plate, the material of the sealing ring is nitrile rubber, so that the perovskite battery device and the encapsulation layer are located on the inner side of the sealing ring to prevent moisture penetration; placing a second cover plate above the encapsulation layer to obtain a perovskite battery element; the first cover plate and the second cover plate are both glass cover plates; Step S8, laminating the perovskite battery element, wherein the lamination temperature of the first cover plate is 80-85°C, the lamination temperature of the second cover plate is 100-105°C, and the lamination time is 30-35s. In order to avoid damage to the battery, after the lamination is completed, the product is placed on a cold plate for rapid cooling to obtain a perovskite battery.

[0031] In this embodiment, during the lamination heat seal, the POE sealant melts, cross-links, and bubbles escape in the internal space between the glass. At this time, the temperature drops slightly due to the heat absorption of POE. Afterwards, the pressure keeps the POE solidified. This packaging method has almost no effect on the open circuit voltage of the perovskite battery, and the device efficiency decay is less than 3%. At the same time, during the packaging process, the packaging temperature is lower than 110°C, and the packaging process does not require ultraviolet irradiation or a vacuum environment, which effectively avoids the potential damage to the perovskite film during the packaging process.

[0032] Comparative Example 1 Step S1, placing the ITO glass in an ultrasonic cleaning tank, and cleaning it with a detergent-deionized water solution, acetone and ethanol for 15 minutes in sequence; drying it with nitrogen, and then treating it with ultraviolet ozone for 15 minutes; Step S2: adding 20 mg / mL −1 The NiOx solution was dropped onto the ITO glass and spin-coated at 2000 rpm for 30 s; and heated at 150°C for 10 min to form a hole transport layer; Step S3, the product obtained in step S2 is transferred to a glove box, and MeO-4PACz dissolved in ethanol is dripped onto the hole transport layer, wherein the concentration of MeO-4PACz is 1.5 mg / mL -1 The film was spin-coated at 4000 rpm for 30 seconds and annealed at 100°C for 10 minutes to form a self-assembled molecular layer. Step S4, drop the CsFAMA ternary perovskite precursor solution on the self-assembled molecular layer, spin-coat at a speed of 1000 rpm for 10 seconds, spin-coat at a speed of 5000 rpm for 40 seconds, and during the spin-coating process, drop 200 μL of ethyl acetate on the spin-coated surface for 12 seconds, transfer the product to a heating platform after the spin-coating is completed, anneal at a temperature of 105-110°C for 20-22 minutes to form a MeO-4PACz film, drop 200 μL of CsFAMA solution at 4000 rpm on the MeO-4PACz film within 2-3 seconds, and anneal at a temperature of 100-110°C for 5-7 minutes to form a light-absorbing layer; Step S5, dripping a mixed solution of [6,6]-phenyl C61 butyric acid methyl ester (PCBM, purity 99%) and fullerene (C60, purity 99.5%) on the light absorbing layer, spin coating at a speed of 3000 rpm for 30 seconds; and annealing at a temperature of 60°C for 5 minutes to form an electron transport layer; Step S6, at 2×10 −6 mbar vacuum condition (effective area 0.1cm 2 ) Using thermal evaporation method, 100nm of Au and 5nm of Cr are sequentially deposited on the electron transport layer to obtain a perovskite cell device; Step S7, placing the perovskite battery device at 4 cm 2 The first cover plate is in contact with the substrate; a copper conductive tape is arranged between the metal electrode layer and the packaging layer, and extends out of the first cover plate, and the thickness of the copper conductive tape is 0.10 mm; a packaging layer is placed on the metal electrode layer; a sealing ring is arranged on the first cover plate, and the material of the sealing ring is nitrile rubber, so that the perovskite battery device and the packaging layer are located on the inner side of the sealing ring to prevent moisture penetration; a 4cm 2 A second cover plate is used to obtain a perovskite battery element; Step S8, laminating the perovskite battery element, wherein the lamination temperature of the first cover plate is 80°C, the lamination temperature of the second cover plate is 100°C, the lamination time is 20s, and after the lamination is completed, the product is placed on a cold plate for rapid cooling to obtain a perovskite battery.

[0033] The perovskite battery obtained in this embodiment was tested, and the test results were as follows: the photoelectric conversion efficiency of the perovskite battery device obtained in this embodiment was 23.27%. Figure 2 It can be seen from the figure that the efficiency of the perovskite battery device obtained in this embodiment decays to 29.9% of the initial efficiency after 1000 hours, and the efficiency loss of the perovskite battery obtained after encapsulation is 6%. Figure 3It can be seen that in the dark state, 25°C and 45±5% relative humidity in air, the device efficiency decays to 52.8% of the initial efficiency after 1000h. Many bubbles are observed on the cover of the perovskite cell, and the surface color is turbid, and the copper conductive tape is not easy to stick and break.

[0034] Example 1 Step S1, placing the ITO glass in an ultrasonic cleaning tank, and cleaning it with a detergent-deionized water solution, acetone and ethanol for 15 minutes in sequence; drying it with nitrogen, and then treating it with ultraviolet ozone for 15 minutes; Step S2: adding 20 mg / mL −1 The NiOx solution was dropped onto the ITO glass and spin-coated at 2000 rpm for 30 s; and heated at 150°C for 10 min to form a hole transport layer; Step S3, the product obtained in step S2 is transferred to a glove box, and MeO-4PACz dissolved in ethanol is dripped onto the hole transport layer, wherein the concentration of MeO-4PACz is 1.5 mg / mL -1 The film was spin-coated at 4000 rpm for 30 seconds and annealed at 100°C for 10 minutes to form a self-assembled molecular layer. Step S4, adding CsFAMA ternary perovskite precursor solution to the self-assembled molecular layer, spin coating at a speed of 1000 rpm for 10 seconds, and spin coating at a speed of 5000 rpm for 40 seconds, and during the spin coating process, adding 200 μL of ethyl acetate dropwise to the spin coating surface for 12 seconds, transferring the product to a heating platform after the spin coating is completed, annealing at a temperature of 105-110°C for 20-22 minutes to form a MeO-4PACz film, and within 2-3 seconds, adding 200 μL of ionic compound 345FAn ammonium ligand (0.5 mgmL-1) in CF solution at 4000 rpm to the MeO-4PACz film, and annealing at a temperature of 100-110°C for 5-7 minutes to form a light absorbing layer; Step S5, dripping a mixed solution of [6,6]-phenyl C61 butyric acid methyl ester (PCBM, purity 99%) and fullerene (C60, purity 99.5%) on the light absorbing layer, spin coating at a speed of 3000 rpm for 30 seconds; and annealing at a temperature of 60°C for 5 minutes to form an electron transport layer; Step S6, at 2×10 −6 mbar vacuum condition (effective area 0.1cm 2 ), 100nm of Au and 5nm of Cr were sequentially deposited on the electron transport layer by thermal evaporation to obtain a perovskite cell device; Step S7, placing the perovskite battery device at 4 cm 2The first cover plate is in contact with the substrate; a copper conductive tape is arranged between the metal electrode layer and the packaging layer, and extends out of the first cover plate, and the thickness of the copper conductive tape is 0.06 mm; a packaging layer is placed on the metal electrode layer; a sealing ring is arranged on the first cover plate, so that the perovskite battery device and the packaging layer are located inside the sealing ring; a 4 cm 2 A second cover plate is used to obtain a perovskite battery element; Step S8, laminating the perovskite battery element, wherein the lamination temperature of the first cover plate is 80°C, the lamination temperature of the second cover plate is 100°C, the lamination time is 20s, and after the lamination is completed, the product is placed on a cold plate for rapid cooling to obtain a perovskite battery.

[0035] The perovskite battery obtained in this embodiment was tested, and the test results were as follows: the photoelectric conversion efficiency of the perovskite battery device obtained in this embodiment was 25.38%. Figure 2 It can be seen from the graph that the efficiency of the perovskite battery device obtained in this embodiment decays to 93.1% of the initial efficiency after 2000 hours. Figure 3 It can be seen that the performance degradation of the perovskite battery is less than 3% compared with the perovskite battery device. Therefore, it can be seen that the packaging strategy of this embodiment can achieve efficient and lossless packaging of the perovskite device. Figure 4 It can be seen that in the dark state, 25°C and 45±5% relative humidity in air, the device efficiency decays to 52.8% of the initial efficiency after 1000h. It can be seen that the present embodiment uses 345FAn to modify the perovskite, and the stability of the perovskite battery changes significantly before and after the modification, indicating that the use of 345FAn to modify the perovskite film effectively improves the environmental stability of the perovskite battery. In addition, many bubbles were observed on the cover plate, and the surface color was turbid, and the copper conductive tape was easy to stick and break.

[0036] Example 2 Step S1, placing the ITO glass in an ultrasonic cleaning tank, and cleaning it with a detergent-deionized water solution, acetone and ethanol for 15 minutes in sequence; drying it with nitrogen, and then treating it with ultraviolet ozone for 15 minutes; Step S2, the concentration is 20mgmL −1 The NiOx solution was dropped onto the ITO glass and spin-coated at 2000 rpm for 30 s; and heated at 150°C for 10 min to form a hole transport layer; Step S3, the product obtained in step S2 is transferred to a glove box, and MeO-4PACz dissolved in ethanol is dripped onto the hole transport layer, wherein the concentration of MeO-4PACz is 1.5 mg / mL -1The film was spin-coated at 4000 rpm for 30 seconds and annealed at 100°C for 10 minutes to form a self-assembled molecular layer. Step S4, drop the CsFAMA ternary perovskite precursor solution onto the self-assembled molecular layer, spin-coat at 1000 rpm for 10 s, spin-coat at 5000 rpm for 40 s, and during the spin-coating process, dropwise add 200 μL of ethyl acetate onto the spin-coated surface for 12 s. After the spin-coating is completed, transfer the product to a heating platform and anneal at 105-110°C for 20-22 min to form a MeO-4PACz film. Within 2-3 seconds, 200 μL of the ionic compound 345FAn ammonium ligand (1.5 mg mL -1 ) in a CF solution and dripped onto the MeO-4PACz film at 4000 rpm, and annealed at a temperature of 100-110°C for 5-7 min to form a light absorbing layer; Step S5, dripping a mixed solution of [6,6]-phenyl C61 butyric acid methyl ester (PCBM, purity 99%) and fullerene (C60, purity 99.5%) on the light absorbing layer, spin coating at a speed of 3000 rpm for 30 seconds; and annealing at a temperature of 60°C for 5 minutes to form an electron transport layer; Step S6, at 2×10 −6 mbar vacuum condition (effective area 0.1cm 2 ), 100nm of Ag was deposited on the electron transport layer by thermal evaporation to obtain a perovskite cell device; Step S7, placing the perovskite battery device at 4 cm 2 The first cover plate is in contact with the substrate; a copper conductive tape is arranged between the metal electrode layer and the packaging layer, and extends out of the first cover plate, and the thickness of the copper conductive tape is 0.15 mm; a packaging layer is placed on the metal electrode layer; a sealing ring is arranged on the first cover plate; a 4 cm 2 A second cover plate is used to obtain a perovskite battery element; Step S8, laminating the perovskite battery element, wherein the lamination temperature of the first cover plate is 85°C, the lamination temperature of the second cover plate is 105°C, the lamination time is 25s, and after the lamination is completed, the product is placed on a cold plate for rapid cooling to obtain a perovskite battery.

[0037] The perovskite cell obtained in this embodiment was tested, and the test results were as follows: the photoelectric conversion efficiency of the perovskite cell device obtained in step S6 was 24.22%, and the perovskite cell had fewer surface bubbles observed on the cover plate, and the surface color was relatively transparent. Compared with the unpackaged device, the efficiency loss of the packaged perovskite cell was 5%, and the packaged device maintained 94.1% of the initial efficiency when operated for 2000h under maximum power point tracking at 50-60℃.

[0038] The above are only preferred embodiments of the present application, and are not intended to limit the patent scope of the present application. Any equivalent structure or equivalent process transformation made using the contents of the present application specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present application.

Claims

1. A highly efficient and stable perovskite solar cell combining ionic compound interface modification and polymer material external encapsulation, characterized in that: It includes a substrate, a hole transport layer, a self-assembled molecular layer, a light absorption layer, an electron transport layer and a metal electrode layer which are stacked in sequence from bottom to top; Wherein, the material of the light-absorbing layer is a perovskite film modified by an ionic compound ammonium ligand, and the material of the perovskite film is a CsFAMA ternary perovskite precursor.

2. The highly efficient and stable perovskite solar cell combining ionic compound interface modification and polymer material external encapsulation according to claim 1, characterized in that: The ionic compound ammonium ligand is 3,4,5-trifluoroaniline hydroiodide.

3. The high-efficiency and stable perovskite solar cell combining ionic compound interface modification and polymer material external encapsulation according to claim 1, characterized in that: Also includes: An encapsulation layer, the encapsulation layer covers the surface of the metal electrode layer, and the material of the encapsulation layer is POE sealant; A first cover plate, located below the base; A second cover plate, covering the packaging layer; Wherein, the first cover plate and the second cover plate are both made of glass.

4. The highly efficient and stable perovskite solar cell combining ionic compound interface modification and polymer material external encapsulation according to claim 1, characterized in that: The substrate is indium tin oxide glass; The material of the hole transport layer is nickel oxide, and the thickness of the hole transport layer is 18-22nm; The material of the self-assembled molecular layer is [4-(3,6-dimethoxy-9H-carbazole-9-yl)butyl]phosphonic acid or (2-(9H-carbazole-9-yl)ethyl)phosphonic acid, and the thickness of the self-assembled molecular layer is 4-6nm; The material of the electron transport layer is a mixture of [6,6]-phenyl C61 butyric acid methyl ester and fullerene, wherein the mass ratio of [6,6]-phenyl C61 butyric acid methyl ester to fullerene is 4:1, and the thickness of the electron transport layer is 50-60nm; The thickness of the light absorbing layer is 745-755 nm.

5. The high-efficiency and stable perovskite solar cell combining ionic compound interface modification and polymer material external encapsulation according to claim 1, characterized in that: The electrode layer includes a silver layer, or a stacked chromium layer and a gold layer, wherein the chromium layer is in contact with the electron transport layer.

6. A method for preparing a highly efficient and stable perovskite solar cell combining ionic compound interface modification and polymer material external encapsulation as claimed in claim 1, characterized in that: include: Spin coating a nickel oxide solution on the substrate to form a hole transport layer; Spin coating a self-assembly solution on the hole transport layer to form a self-assembly molecular layer; Spin coating a perovskite precursor solution on the self-assembled molecular layer to form a perovskite film, and dripping an ionic compound ammonium ligand solution on the perovskite film to form a light absorbing layer; Spin coating a mixed solution of [6,6]-phenyl C61 butyric acid methyl ester and fullerene on the light absorbing layer to form an electron transport layer; Depositing a metal electrode layer on the electron transport layer to obtain a perovskite battery device; Placing the perovskite cell device on a first cover plate, wherein the first cover plate is in contact with a substrate; Placing a packaging layer on the metal electrode layer, and providing an electrode between the metal electrode layer and the packaging layer; wherein the material of the packaging layer is POE sealant; A sealing ring is arranged on the first cover plate so that the perovskite battery device and the encapsulation layer are located inside the sealing ring; a second cover plate is placed above the encapsulation layer to obtain a perovskite battery element; The perovskite battery element is laminated, wherein the lamination temperature of the first cover plate is 80-85°C, the lamination temperature of the second cover plate is 100-105°C, and the lamination time is 30-35s, to obtain a perovskite battery.

7. The method for preparing a highly efficient and stable perovskite solar cell combining ionic compound interface modification and polymer material external encapsulation according to claim 6, characterized in that: The formation process of the light-absorbing layer is as follows: The CsFAMA ternary perovskite precursor solution is dripped onto the self-assembled molecular layer, and the film is spin-coated at a rotation speed of 1000-1100 rpm for 10-12 s, and at a rotation speed of 5000-5100 rpm for 40-42 s, and annealed at a temperature of 105-110° C. for 20-22 min to form a perovskite film; wherein, during the spin coating process, an anti-solvent is dripped onto the spin coating surface; At a rotation speed of 3500-4000 rpm, an ionic compound ammonium ligand solution is dripped onto the perovskite film, and annealed at a temperature of 100-110° C. for 5-7 minutes to form a light absorbing layer.

8. The method for preparing a highly efficient and stable perovskite solar cell combining ionic compound interface modification and polymer material external encapsulation according to claim 6, characterized in that: The spin coating process of the hole transport layer is as follows: The nickel oxide solution is dropped onto the substrate, and the substrate is spin-coated at a rotation speed of 2000-2500 rpm for 30-35 seconds; and heated at a temperature of 150-155° C. for 10-20 minutes.

9. The method for preparing a highly efficient and stable perovskite solar cell combining ionic compound interface modification and polymer material external encapsulation according to claim 6, characterized in that: The spin coating process of the self-assembled molecular layer is as follows: The self-assembly solution is dripped onto the hole transport layer, and spin-coated at a rotation speed of 3000-4000 rpm for 30-35 seconds; and annealed at a temperature of 100-110° C. for 10-15 minutes.

10. The method for preparing a highly efficient and stable perovskite solar cell combining ionic compound interface modification and polymer material external encapsulation according to claim 6, characterized in that: The spin coating process of the electron transport layer is as follows: A mixed solution of [6,6]-phenyl C61 butyric acid methyl ester and fullerene is dropped onto the light absorbing layer, spin coated at a rotation speed of 3000-3500 rpm for 30-35 seconds, and annealed at a temperature of 60-65° C. for 5-7 minutes.

Citation Information

Patent Citations

  • Packaging structure of anti-creep perovskite solar cell module and packaging method thereof

    CN109427977A

  • Packaged perovskite solar cell and packaging method

    CN111261784A

  • Hole transport layer prepared from mesoporous nickel oxide and self-assembly material, perovskite solar cell formed by hole transport layer and preparation method of perovskite solar cell

    CN117241640A

  • Perovskite cell, preparation method thereof and photovoltaic module

    CN117500284A

  • Composite hole transport layer, inverted perovskite solar cell and preparation method of inverted perovskite solar cell

    CN118488771A

Cited By

  • Perovskite battery assembly and packaging method

    CN122206075A